Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.jegh.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Symptom clusters on primary care medical service trips in five regions in Latin America

Abstract: Short-term primary care medical service trips organized by the North American non-governmental organizations (NGOs) serve many communities in Latin America that are poorly served by the national health system. This descriptive study contributes to the understanding of the epidemiology of patients seen on such low-resource trips. An analysis was conducted on epidemiologic data collected from anonymized electronic medical records on patients seen during 34 short-term medical service trips in five regions in Ecua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 5 publications
2
17
0
1
Order By: Relevance
“…In a previous study conducted in the Monti Cristi region of the Dominican Republic, 18.6% of individuals reported experiencing general pain (back pain, nonspecific headaches, general pain, non-specific muscle strain and osteoarthritis). In addition, general pain was the most frequently reported symptom [37]. The current study is similar to this larger study in which the majority of individuals reported experiencing musculoskeletal complaints.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In a previous study conducted in the Monti Cristi region of the Dominican Republic, 18.6% of individuals reported experiencing general pain (back pain, nonspecific headaches, general pain, non-specific muscle strain and osteoarthritis). In addition, general pain was the most frequently reported symptom [37]. The current study is similar to this larger study in which the majority of individuals reported experiencing musculoskeletal complaints.…”
Section: Discussionsupporting
confidence: 84%
“…The current study is similar to this larger study in which the majority of individuals reported experiencing musculoskeletal complaints. The findings from these two prior studies [36,37] combined with ours are helpful to generate hypotheses of the association between musculoskeletal conditions and disability in low-and middle-income countries. It is important for clinicians and researchers to understand the associations between these conditions to ensure that appropriate educational, patient referral networks and management strategies can be implemented at the WSC clinic.…”
Section: Discussionmentioning
confidence: 79%
“…Of course, pain is the presenting symptom of the majority of the problems a physician sees. In one study, on 22,977 primary care patients, seen in "lowresource" communities, the most common presenting symptoms were general pain, upper respiratory tract symptoms, skin disorders, eye irritation, dyspepsia, and nonspecific abdominal complaints [1]. With increasing frequency, the Emergency Department is being used to replace the primary care physicians [2].…”
Section: Opinionmentioning
confidence: 99%
“…3,4 Skin disorders such as scabies, fungal infections, and pyoderma are examples of disease processes that are commonly encountered during MSTs but less frequently seen by volunteer clinicians in their home settings. 5,6 In one epidemiological study, superficial mycosis accounted for 1.4-4.2% of patient diagnoses on five MSTs located in Ecuador, Guatemala, and Dominican Republic, 7 and studies based on mycological examinations indicate a prevalence of 7-33% in children in Africa. [8][9][10][11][12][13][14] Likewise, the prevalence of pyoderma (i.e., impetigo, cellulitis, abscesses) is approximately 5-10% in tropical regions, according to the World Health Organization (WHO).…”
Section: Introductionmentioning
confidence: 99%